Risk Management Strategy Implementation for Business Plan at Imported Beef Supply Startup - Syina, Ibnu; Syah, Tantri Yanuar Rahmat; Kustiawan, Unggul; Nofierni, Nofierni (Journal La Bisecoman, 2025)
This study is concerned with how to develop and carry out a risk management strategy at PT Meat Tech, a startup in the imported beef business. Following the ISO 31000:2018 standard, the research uses a qualitative-descriptive strategy to spot, review, assess and tackle risks within the organization. The research finds that PT Meat Tech deals with significant weaknesses in operations, human assets and finances. A risk assessment matrix helped the company score and prioritize threats which led to the planning of targeted solutions, division of tasks and checking risk levels after these measures were carried out. The research points out that structured plans improve alignment and accountability, but note they do not always work as intended when faced with resource issues. According to the study, although PT Meat Tech grasps the concepts of risk governance well, the sustainability is linked to always adapting, making investments and introducing real-time monitoring. Using these lessons, SMEs specializing in high-risk, logistics-based operations can create and strengthen their systems for handling risks.